Pengembangan Instrumen Penilaian Higher Order Thingking Skills (HOTS) pada Pembelajaran IPA Siswa Kelas IV SDN 21 Bengkulu Tengah - Rinto Hartono; Endang Widi Winarni; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to analyze the logical feasibility, empirical and student learning outcomes profile. The product of developing the HOTS Assessment Instrument in Class IV Science Learning at SDN 21 Bengkulu Tengah. This research is a Research and Development (R&D) study. The model used in development is the ADDIE model. The subjects in the study were students of SD Negeri 21 Bengkulu Tengah, totaling 20 students in grade IV. The instrument used in this study was an interview guide, and the concept comprehension test was in the form of multiple choice questions. To measure the logical and empirical feasibility of conceptual understanding, it was carried out on fourth grade elementary school students. The data analysis technique in this study is validation analysis using Aiken's V and Interrater Reliability, as well as quantitative analysis using the research profile. From the results of the research it is known that the results of material, language, and design validation of the assessment on HOTS questions are very feasible and well used in learning so that students are happy and interested in learning. The results of this study only calculate the value of success, namely the profile of student learning outcomes answering the level of C4 82% and C5 77.50% in terms of multiple choice questions.